Hepatic and Renal Lesions in Free Ranging Black Caimans (Melanosuchus niger) in the Brazilian Amazon for Human Consumption - Cardoso, Adriana Maciel de Castro; Souza, Alex Junior Souza de; Menezes, Rodrigo Caldas; Souza, Natália Freitas de; Pereira, Washington Luiz Assunção; Tortelly, Rogério (Acta Scientiae Veterinariae, 2018)
Background: The black caiman (Melanosuchus niger), belongs to the order Crocodylia, family Alligatoridae. More than a hundred species of helminths, mainly trematodes and nematodes, parasitize crocodilians around the world and a considerable number of species of ascaris have been described in crocodilians. There are few descriptions of hepatic and renal diseases affecting M. niger, and no articles related to the histopathological aspects of this species were found. The aim of this study was to evaluate gross and microscopically the liver and kidneys of 100 specimens of Melanosuchus niger slaughtered in Reserva de Desenvolvimento Sustentável Mamirauá, from natural populations. Materials, Methods & Results: The capture of the alligators was performed during the night, by members of the community itself in the channels and lagoons of the Reserve's lowland ecosystem. For the capture procedures, ties and harpoons were used and the animals were identified through the red glow of the eyes using the spot light lanterns. After being conducted to the slaughter area, the animals were submitted to the previous biometry to select which animals were appropriated for slaughter, they should measure between 2.10 m and 2.80 m. A total of 88 livers and 95 kidneys of M. niger of natural populations were analysed gross and microscopically, independently of gross lesions. The fragments collected for histopathological examination were approximately 0.5 cm thick and they were packed in appropriated identified containers with formalin 10% solution. The collection procedures were accompanied by field records for data recording. After fixation of the collected material, it were processes by habitual techniques for paraffin inclusion and hematoxylin-eosin staining. Grossly, none of the livers examined presented alterations and two kidneys presented parasitism. The hepatic microscopic analysis indicates in 3/88 cases, multiple foci of necrosis. In 7/88 cases, it was observed in the hepatic parenchyma, granulomas, mainly with epithelioid cells. In the histopathological examination of the kidney, the only alteration observe in 8/95 cases was the presence of granulomas. Discussion: The occurrence of Sebekia oxycephala nymphs, a pentastomid, in the liver of Alligator mississippiensis was reported in other researches. The parasite Sebekia mississippiensis was observed in liver and lungs of A. mississippiensis. similar alterations were also noticed in this research. The coccidiosis related to hepatic manifestations in crocodilians is related to the parasite that may belong to the genus Goussia. In the liver, under the oocysts form leads to a diffuse hydropic degeneration of hepatocytes. In this study it was also observed the hydronic degeneration, however, associated to the necrosis areas that had in the periphery epithelioid cells infiltrated, without parasitic participation. Two renal trematodes are known in crocodilians, Deurithrema gingae and Renivermis crocodyli both in Crocodylus porosus. Also it was found in the renal parenchyma few encapsulated and well delimited parasites by a severe tissue reaction. Based on the gross and microscopic found, it is concluded that liver and kidney, although multiple organ functions, were not prone to infections, with granulomas being the main manifestation, and the etiopathogenesis of the areas of hepatic necrosis could not be defined.